2020
DOI: 10.1371/journal.pone.0226894
|View full text |Cite
|
Sign up to set email alerts
|

Low risk pregnancies after a cesarean section: Determinants of trial of labor and its failure

Abstract: in women with less than 11 years of education, and in women of non-western origin. The effects of health system factors, i.e. delivery unit size and administrative region were considerable, on both TOLAC and TOLAC failure. The effects of several determinants changed significantly (P < 0.05) from 1989-2002 to 2003-2014: The association between non-TOLAC and maternal age > 39 years became weaker, the association between short education and TOLAC failure became stronger, and the association between TOLAC failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In a retrospective study published in 2020( 22 ), the authors investigated the effect of demographic, socioeconomic, and health system factors on TOLAC and TOLAC failure in low risk pregnancies, and their variation over time. Advanced maternal age was associated with both low TOLAC rates and high TOLAC failure, while ethnicity (women from East Asia, Latin America, non-western origin), education (<11 years of education) and health system factors (e.g., delivery unit size and administrative region) had a considerable effect on both TOLAC and TOLAC failure.…”
Section: Risk Factor Rankingmentioning
confidence: 99%
“…In a retrospective study published in 2020( 22 ), the authors investigated the effect of demographic, socioeconomic, and health system factors on TOLAC and TOLAC failure in low risk pregnancies, and their variation over time. Advanced maternal age was associated with both low TOLAC rates and high TOLAC failure, while ethnicity (women from East Asia, Latin America, non-western origin), education (<11 years of education) and health system factors (e.g., delivery unit size and administrative region) had a considerable effect on both TOLAC and TOLAC failure.…”
Section: Risk Factor Rankingmentioning
confidence: 99%
“…Therefore, for obstetricians, it is crucial to identify the potential protective and risk factors influencing a woman’s successful VBAC based on the patients’ baseline characteristics. Several studies have reported that patient demographic characteristics (patient race and ethnicity, education level and gestational week), 11 12 maternal factors (maternal age, body mass index, bishop score, diabetes, hypertensive disorders complicating pregnancy and previous vaginal deliver), 12–15 fetal factors (estimated birth weight) 16 and other related factors (oxytocin implementation) 15 that may be associated with a woman’s chance for successful VBAC. Some predictive models for successful VBAC have also been published in recent years.…”
Section: Introductionmentioning
confidence: 99%